NILAI LUHUR DALAM LAGU-LAGU DAYAK: KAJIAN IMPLIKATUR - Yuni, Brigita (Jurnal KATA, 2018)
This study aims to describe the form and meaning of the noble value in the tribal pop tribe Dayak. Sources of data in this study poetry song pop area Dayak tribe. The data in the study is the lyrics of regional pop songs that allegedly contain noble value implicatures. Techniques of collecting data using references, notes, and interviews. Methods of data analysis using the method padan with basic techniques select the determinants and advanced techniques of appeal. Based on the results of research, the forms and meanings of the noble values are classified into (1) self-related values including (a) responsibility, (b) courage, (c) thinking ahead, and (d) hard work. (2) The values associated with each other include values (a) respect, (b) caring, (c) love of the homeland, and (d) courtesy. (3) The values associated with nature include the value of (a) appreciating natural health, and (b) preserving culture. (4) God-related values include (a) being grateful.Penelitian ini bertujuan untuk mendeskripsikan wujud dan maksud nilai luhur dalam lagu pop daerah suku Dayak. Sumber data dalam penelitian ini syair lagu pop daerah Suku Dayak. Data dalam penelitian adalah lirik lagu pop daerah yang diduga mengandung implikatur nilai luhur. Teknik pengumpulan data menggunakan simak, catat, dan wawancara. Metode analisis data menggunakan metode padan dengan teknik dasar pilih unsur penentu dan teknik lanjutan hubung banding. Berdasarkan hasil penelitian wujud dan maksud nilai luhur diklasifikasikan menjadi (1) nilai yang berhubungan dengan diri sendiri meliputi (a) tanggung jawab, (b) keberanian, (c) berpikir jauh ke depan, dan (d) kerja keras. (2) Nilai yang berhubungan dengan sesama meliputi nilai (a) hormat, (b) peduli, (c) cinta tanah air, dan (d) sopan santun. (3) Nilai yang berhubungan dengan alam meliputi nilai (a) menghargai kesehatan alam, dan (b) melestarikan budaya. (4) Nilai yang berhubungan Tuhan meliputi nilai (a) bersyukur.